Boosting Income for Magelang's Creative Sector (Efficient: Indonesian Journal of Development Economics, 2024)
Production activities that can still survive and achieve large profits today are activities that are competitive and innovative. The current sector that continues to grow, one of the factors that increase economic growth is the creative economy sector, which shows improvement in increasing the income of its people. The creative economy is a strategy implemented by the Indonesian government in advancing the country's economic sector. This study aims to analyze the factors that affect the income of creative economy business actors in Magelang Regency. This study uses multiple linear regression analysis tools. The results showed that labor, gender, and creative economy subsector had a significant effect on the income of creative economy business actors. While capital, length of business, education, skills, and marketing have no significant effect on the income of creative economy business actors. The implication of this research is that it is necessary to increase investment in labor development, training and capacity building in order to increase productivity and efficiency